Fluid-structure Coupling Simulation Analysis of Angular Contact Ball Bearing - Lanwen Wang; Xuanyu Sheng; Jianbin Luo (Jixie chuandong)
The lubrication condition of angular contact ball bearings in operation is crucial，and the lubricant directly affects the contact state of rolling bearings. In order to analyze the lubrication condition of angular contact ball bearings and the mechanical characteristics of bearings considering lubrication，based on finite element method and Lattice-Boltzmann method， the bidirectional fluid-structure coupling simulation model of bearings is established. The dynamics finite element simulation and lubricating fluid simulation of angular contact ball bearings are carried out，and the results are compared with the calculation results of bearing quasi-static theory to verify the accuracy of the model. The results show that the cage is in contact with the ball and hits，the oil film pressure is the largest in the bearing cavity，and the contact areas of the ball with the inner ring and the outer ring raceway are the second and third largest oil film pressure areas respectively. The lubricating oil is affected by the revolution of the ball and flows along the direction of rotation of the ball to achieve lubrication between the ball and inner ring，outer ring and cage. The simulation results of ball motion and maximum contact stress are consistent with the solution results of bearing quasi-static theory，that is，the fluid-structure coupling simulation model has high accuracy in calculating the mechanical characteristics of bearings.